2022
DOI: 10.1186/s12905-022-01608-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of theory-based education on promoting a healthy lifestyle in pre-diabetic women: RCT

Abstract: Background Due to the fact that pre-diabetic people are at higher risk of developing diabetes, it is possible to reduce the risk by taking preventive measures. Therefore, the present study aimed to determine the effect of theory-based education on promoting a healthy lifestyle and fasting blood sugar (FBS) in pre-diabetic women. Methods This is a cluster‐randomized controlled trial that was performed on 71 pre-diabetic women referred to Arak Compre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
1
1
1
Order By: Relevance
“…After the intervention, the attitude score for regular PA within the intervention group was significantly increased in this study, consistent with the findings of another TPB-based intervention done on prediabetic women [ 44 ]. This showed that the intervention reinforced the beliefs and attitudes of secondary school teachers, which further contributed to school teachers having a higher tendency to perform PA.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…After the intervention, the attitude score for regular PA within the intervention group was significantly increased in this study, consistent with the findings of another TPB-based intervention done on prediabetic women [ 44 ]. This showed that the intervention reinforced the beliefs and attitudes of secondary school teachers, which further contributed to school teachers having a higher tendency to perform PA.…”
Section: Discussionsupporting
confidence: 90%
“…Perceived behavioural control after intervention in this study was not significantly improved as in another study [44]. No improvement in perceived behavioural control showed that the school teachers did not consider themselves more capable of doing PA.…”
Section: Discussioncontrasting
confidence: 77%
“…In the study of MohammadniaMotlagh et al . [ 35 ] and Parrott et al ,[ 36 ] the perceived behavioral control increased after the intervention compared to the pre-test. In Kelley’s intervention,[ 37 ] the perceived behavioral control after the educational intervention in the intervention group increased significantly compared to the control group, and it sustained after the follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is no study on lifestyle changes in patients with NAFLD using health education based on behavioral models. On the other hand, studies not only introduce TPB as a suitable model to explain lifestyle intentions and behaviors but also consider it as an effective model for improving the lifestyle of patients with diabetes, obesity, and cardiovascular disease [ 22 24 ]. TPB suggests that the main determinant of behavior is the intention of an individual to be involved in behavior and perceived control over behavior [ 25 ].…”
Section: Introductionmentioning
confidence: 99%